Reoxidation of graphene oxide: Impact on the structure, chemical composition, morphology and dye adsorption properties - Zito, Cecilia A. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Mazon, Talita; Dippel, Ann-Christin; Koziej, Dorota; Volanti, Diogo P. [UNESP] (Elsevier, 2021)
The chemical composition, oxidation degree, and sheet size strongly affect the properties of graphene oxide (GO). Therefore, much effort has been directed to improve the synthesis of GO and control its structure. Herein, we report the reoxidation of GO using milder conditions of a modified Hummers’ method, including shorter reaction times and a reduced proportion of chemicals to obtain the reoxidized GO (Ox-GO). The reoxidation impact was evaluated by studying the materials’ adsorption performance towards methylene blue (MB) and rhodamine B (RB). Compared to GO, Ox-GO presents a similar C/O ratio, increased interlayer spacing, smaller sheets with holes, a higher exfoliation degree, and slight differences in each oxygenated functional group. Our measurements evidence that Ox-GO has an MB adsorption capacity more than 30% higher than GO under different conditions of dye concentration and pH. Moreover, Ox-GO also shows a notable improvement in the RB removal for a high dye concentration, where the removal capacity is almost 40% higher than that of GO. The enhancements in the dyes’ removal are attributed to the increased accessible surface area of Ox-GO, which provides more sites for dyes’ adsorption.
Keywords: Cationic dye; Graphite oxide; Pair distribution function; Total X-ray scattering; Water treatment